PROFESSIONAL EXAMINATIONS. - Chamberlain, Henry T.; Chamberlain, John H. (The Accounting Review, 1959)
The article presents a list of problems that were prepared by the Board of Examiners of the American Institute of Certified Public Accountants (CPA) and were presented as the second half of the CPA examination in accounting practice on November 6, 1958. The candidates were required to solve problems 1, 2, 3 and 4 and either problem 5 or problem 6. The total weight assigned to this section of the examination in accounting practice was 50 points and the examiners point out that the suggested time allowances given below was approximately proportional to the point value of the various problems.